Isolation and characterization of human DNA fragments with nucleotide sequence homologies with the simian virus 40 regulatory region. - Conrad, S E (1982)
A recombinant library of human DNA sequences was screened with a segment of simian virus 40 (SV40) DNA that spans the viral origin of replication. One hundred and fifty phage were isolated that hybridized to this probe. Restriction enzyme and hybridization analyses indicated that these sequences were partially homologous to one another. Direct DNA sequencing of two such SV40-hybridizing segments indicated that this was not a highly conserved family of sequences, but rather a set of DNA fragments that contained repetitive regions of high guanine plus cytosine content. These sequences were not members of the previously described Alu family of repeats and hybridized to SV40 DNA more strongly than do Alu family members. Computer analyses showed that the human DNA segments contained multiple homologies with sequences throughout the SV40 origin region, although sequences on the late side of the viral origin contained the strongest cross-hybridizing sequences. Because of the number and complexity of the matches detected, we could not determine unambiguously which of the many possible heteroduplexes between these DNAs was thermodynamically most favored. No hybridization of these human DNA sequences to any other segment of the SV40 genome was detected. In contrast, the human DNA segments isolated cross-hybridized with many sequences within the human genome. We tested for the presence of several functional domains on two of these human DNA fragments. One SV40-hybridizing fragment, SVCR29, contained a sequence which enhanced the efficiency of thymidine kinase transformation in human cells by approximately 20-fold. This effect was seen in an orientation-independent manner when the sequence was present at the 3' end of the chicken thymidine kinase gene. We propose that this segment of DNA contains a sequence analogous to the 72-base-pair repeats of SV40. The existence of such an "activator" element in cellular DNA raises the possibility that families of these sequences may exist in the mammalian genome.